2013
DOI: 10.1080/14888386.2013.848824
|View full text |Cite
|
Sign up to set email alerts
|

Macrofungal diversity and ecology of the mangrove ecosystem in the Indian part of Sundarbans

Abstract: Sundarbans, the world's largest mangrove biomes, have a rich biodiversity of diverse flora and fauna. Although various attempts had been made previously to explore the diversity of this World Heritage Site, information related to the diversity and ecology of macrofungi in this region is sparse. In this context, the aim of this study was to record the macrofungal diversity and describe the macrofungal communities of this ecosystem whose lifecycles are intricately woven with the mangrove ecosystem of the Indian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
2

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Solvents were distilled and dried before use. The ligands 3-(4-Pyridyl)-triazoline-5-thione (PytTH) and 3-(4'-Pyridyl)-4-phenyltriazoline-5-thione (PPytTH) were prepared by the method of Dutta et al 17 . The ligands were recrystallized from ethanol before use.…”
Section: Methodsmentioning
confidence: 99%
“…Solvents were distilled and dried before use. The ligands 3-(4-Pyridyl)-triazoline-5-thione (PytTH) and 3-(4'-Pyridyl)-4-phenyltriazoline-5-thione (PPytTH) were prepared by the method of Dutta et al 17 . The ligands were recrystallized from ethanol before use.…”
Section: Methodsmentioning
confidence: 99%
“…In the last 10 years, our research time has conducted extensive field work and inventoried a large number of wild mushrooms from different corners of the state with the active help from ethnic and tribal mushroom hunters of the regions (Pradhan et al, 2012; Dutta et al, 2013). Morphological and molecular investigation revealed that many of them are new to science (Acharya, Dutta & Pradhan, 2012; Dutta et al, 2014), new to the record for India (Dutta et al, 2011; Dutta et al, 2012a) and additionly to the macrofungal flora of West Bengal (Dutta et al, 2012b; Acharya et al, 2014), while some of the remaining mushrooms were revealed not to be currently documented as edible mushroom.…”
Section: Introductionmentioning
confidence: 99%
“…Since last 10 years, extensive field work by our research team inventoried large number of wild mushrooms from different corner of state with active help from the ethnic and tribal mushroom hunters of the regions (Pradhan et al, 2012;Dutta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%